IMPLEMENTATION OF DIGITAL MARKETING AS A MARKETING COMMUNICATION STRATEGY THROUGH INSTAGRAM SOCIAL MEDIA BY THE JAKARTA VESPA SCHOOL UMKM WORKSHOP - Endang Supriyadi; Maya Sofiana; Syaihan Alfalah (Ikatan Dosen Menulis, 2026)
Competition and technological development are very progressive. Micro, Small and Medium Enterprises (MSMEs) must be able to innovate with digital technology in order to compete competitively. However, not all MSMEs optimize digital technology in this case Instagram. The purpose of this study is to determine the Implementation of Digital Marketing as a Marketing Communication Strategy through Instagram Social Media by MSMEs Bengkel Vespa School Jakarta, to find out what obstacles are faced by the Implementation of Digital Marketing as a Marketing Communication Strategy through Instagram Social Media by MSMEs Bengkel Vespa School Jakarta and to find out what efforts are made in the Implementation of Digital Marketing as a Marketing Communication Strategy through Instagram Social Media by MSMEs Bengkel Vespa School Jakarta. Data collection techniques are based on direct observation and in-depth interviews with informants. Data analysis techniques with Miles and Huberman in Miles and Huberman. The results of the study that the Implementation of Digital Marketing as a Marketing Communication Strategy through Instagram Social Media by MSMEs Bengkel Vespa School Jakarta are not optimal but the existing obstacles are not felt to be too significant. The SWOT results reveal potential strengths and opportunities, but also show weaknesses and threats that need to be addressed.